Shipwrecks of Feasibility in the Field of Investment Business - Bintang Parashtheo; Akhmad Budi Cahyono (IHSA Institute, 2023)
Indonesian Valuable Objects on the Load of Sinking Ships (BMKT) have a large potential. This makes the ships buried in Indonesian territorial seas a tremendous resource. Illegal treasure hunters have targeted Indonesia's BMKT because to its great potential, causing considerable losses. Realizing this, it is vital to pay attention to Valuable Items on the Load of Sinking Ships (BMKT) and develop rules to maximize their potential. This study aims to analyze the policies governing BMKT to support investors in participating in investing in the business sector of BMKT management and creating BMKT management that is optimal and feasible for all aspects of the values contained in the BMKT itself. The approach method used to achieve this research is an approach focused on regulations or policies (statute approach) and conceptual analysis. The result showed that there is still substantial overlap between regulations controlling BMKT, making BMKT administration feasible. In spite of this, the Economic Analysis of Law is used to explain the expansion of the legal dimension through its studies. In addition, the economic value and cultural legacy of BMKTs that cannot be appointed due to the difficulties of appointment or the impossibility of relocation may be used on-site via marine tourist activities, notably diving tourism. As such, investors who wish to participate in the business sector of BMKT management may use BMKT more properly and optimally, including local and international investors.